Principles of creation a Common Data Environment of an information model of building object in a cloud service - M. A. Gvozditsky; Yu. V. Ogorodnova; D. S. Leytes (Архитектура, строительство, транспорт)
Construction industry of Russia according to a number of federal initiatives is preparing to transit to information modeling technologies. This article considers the basic key concepts of digital transformation (information model and Common Data Environment), reveals the importance and necessity of using the Common Data Environment for capital construction project participants, provides a list of existing domestic developments and describes in detail the principles of construction, the essence and main advantages of one of them (Pilot-BIM) based on the studied literature sources.